Investigation of factors that cause insulin precipitation and/or amyloid formation in insulin formulations - Yui Ohno; Tomohiro Seki; Yu Kojima; Ryotaro Miki; Yuya Egawa; Osamu Hosoya; Keizo Kasono; Toshinobu Seki (BMC, 2019)
Abstract Background Multiple daily subcutaneous injections (MDSIs) are mainly used for formulating an insulin therapy for diabetic patients; however, they also cause insulin-derived amyloidosis (IDA) and lead to poor glycemic control. In addition, for the continuous subcutaneous insulin infusion system (CSII), precipitation frequently causes catheter occlusion and, if the precipitate in the formulations is amyloid, the injection of the insoluble amyloid into the subcutaneous tissue leads to IDA. The aim of this study was to conduct in vitro experiments and present a situation where insulin formulations cause precipitation and amyloid formation. Methods Humulin®R and NovoRapid® were used as model formulations for MDSIs and CSII, respectively. The generation of the precipitation was evaluated by measuring turbidity, and amyloid formation was evaluated by using Thioflavin T. Humulin®R was mixed with saline buffer solutions and glucose solutions to evaluate the effect of dilution. In addition, we created an experimental system to consider the effect of the time course of condition changes, and investigated the effects of insulin concentration, m-cresol existence, and pH change on the generation of the precipitate and amyloid in the formulation. Results In both the original and diluted formulations, physical stimulation resulted in the formation of a precipitate, which in most cases was an amyloid. The amyloid was likely to be formed at a near neutral pH. On the contrary, although a precipitate formed when the pH was decreased to near the isoelectric point, this precipitate was not an amyloid. Further decreases in pH resulted in the formation of amyloids, suggesting that both the positive and negative charged states of insulin tended to form amyloids. The formulation additive m-cresol suppressed amyloid formation. When additives were removed from the formulation, the amyloid-containing gel was formed in the field of substance exchange. Conclusions To consider changes in conditions that may occur for insulin formulations, the relationship between the formation of precipitates and amyloids was demonstrated in vitro by using insulin formulations. From the in vitro study, m-cresol was shown to have an inhibitory effect on amyloid formation.